Determination of nurses' quality of work life and influencing factors - (:unkn) unknown (AVES PRESS LTD, 2015)
Objective: This study was conducted as a descriptive study and aimed to determine nurses' quality of work life (QWL) and the influencing factors. Method: The study was conducted with 310 nurses working at nine private hospitals and three training and research hospitals in Istanbul between March and June 2013. Data were collected with the Nurses Data Sheet containing the socio-demographic characteristics of nurses and with the Quality of Nursing Work Life Scale (QNWL). The percentage, arithmetic mean, standard deviation, One-way ANOVA, Tukey's HSD, Student t, Kruskal-Wallis, Mann-Whitney U test and chi-squared tests were used to assess data. Results: The Cronbach's Alpha coefficient of nurses in QNWL was found to be 0.89 and the mean score of the scale was determined to be at a good level (110.35 +/- 19.35). The mean score of QNWL of the nurses working at private hospitals was at a good level (115.12 +/- 19.12) whereas it was found to be at a medium level (105.12 +/- 18.12) at training and research hospitals. The highest QNWL subscale score of nurses was obtained in work conception subscale with a score of 3.50 +/- 0.65 at training and research hospitals and 3.68 +/- 0.63 at private hospitals. On the other hand, the lowest score was obtained in working environment subscale (2.59 +/- 0.78) at training and research hospitals and in working conditions subscale (3.02 +/- 0.50) at private hospitals. It has been determined that age group and educational status, which are among the descriptive characteristics of nurses, and the institution they work, monthly salary, professional working period and working period at the institution, weekly working hours, the presence of workflow chart, the presence of career aims at the institution, choosing the profession willingly, the desire to leave the institution, participation in the decisions taken and the fairness of nurse managers to nurses, which are among the professional characteristics, affected the QNWL subscales and there were statistically significant difference between them (p<0.05). Conclusion: The QWL of nurses in general and of the nurses working at private hospitals was determined to be at a good level, whereas the QWL of nurses working at training and research hospitals was at a medium level. It is suggested to conduct required activities by the health care institution managers so as to improve work life conditions of the nurses working at training and research hospitals in particular and to support the nurses in order to improve their QWL.
Keywords: nursing; quality of work life; quality